Towards climate and water smart Olive system in Morroco C4S olive irrigation decision support pool - Mohamed Hakin Kharrou; Abedeleghani Chehouni (2023)
This multiscale irrigation decision tool aims at helping Farmers and agriculture/water managers at basin level get better yield predictions according to water and climate stress to guide scaling of new water saving irrigation techniques with minimal productivity trade-off. Experiment and C4S yield gap prediction tool development in good progress. Drought impact study on olive systems in past years (6th consecutive agronomic year)Living lab set up. Extension strategy discussed with Altmoutmir (potential outreach 3500 farmers) and IRD/Naila (transfer Citrig advisory app Tunisia/Morocco).